Belarus at the United Nations: assessing its political track record - Makei, Vladimir V. (Journal of the Belarusian State University. International Relations, 2020)
There is much focus on the United Nations in 2020 as it celebrates its 75th anniversary, which, in turn, generates many expectations from the organization. The UN, however, can do only as much as it is allowed by its institutional building. In particular, it is much constrained to deliver on the so-called first-tier peace and security cluster, whereas it can do far more on the second-tier non-security issues. Belarus has been engaged with the UN since 1945 with a variable degree of success. Belarus’ most conspicuous involvement in the United Nations has been taking place since 2005 as a result of its unifying initiatives.